2004
DOI: 10.1111/j.1525-1497.2004.21249.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of screening and treatment for depression in ambulatory indigent patients

Abstract: OBJECTIVE:To determine the effectiveness of screening and treatment for depression among ambulatory indigent patients visiting resident physicians. DESIGN: Two-group randomized trial ( N = 33 intervention, N = 28 usual care) with baseline, 6-month, and 12-month outcome measurements. SETTING: Internal Medicine Residency Clinic. PATIENTS:Clinic patients over 18 years of age who screened positive for depression on the PRIME-MD during a visit to their resident physician. Patients were not receiving treatment nor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…At the same time, active screening for depression within already burdened and under-resourced public care systems raises additional considerations, including the potential high prevalence of depression symptoms frequently found in low-income and medically underserved populations [63][64], the needs and preferences of culturally diverse patients [65][66], and lack of availability of low cost depression care in the community [26,67]. Despite these considerations, screening can be effective for indigent patients [68].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, active screening for depression within already burdened and under-resourced public care systems raises additional considerations, including the potential high prevalence of depression symptoms frequently found in low-income and medically underserved populations [63][64], the needs and preferences of culturally diverse patients [65][66], and lack of availability of low cost depression care in the community [26,67]. Despite these considerations, screening can be effective for indigent patients [68].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this underdiagnosis likely parallel those found in general primary care settings where depression is also frequently underdiagnosed. A number of studies have shown that providers' use of guidelines along with a thorough follow-up program in primary care settings can facilitate successful identification and treatment of patients with depression [129][130]. Two frequently cited guidelines for depression treatment were published in 1993 by the Agency for Health Care Policy and Research (AHCPR) [131] and the American Psychiatric Association [132].…”
Section: Use Of Depression Guidelinesmentioning
confidence: 99%
“…[20][21][22][23] According to the task force, these trials "screened all patients for depression, enrolled only those screening positive, and returned results of screening to clinicians in the intervention group only." 10 The USPSTF told The BMJ that, if anything, this would have led to more conservative estimates of screening benefit.…”
Section: Featurementioning
confidence: 99%
“…24 Critics point out, however, that none of the four studies included an unscreened control group, and three of the studies compared optimized with usual care, meaning that any benefit in health outcomes could be because of optimized care and not screening (though not all found a benefit). [20][21][22][23] The fourth study provided usual care to both arms but found that the intervention arm, in which providers were told of screening results, "did not lead to improved patient outcomes." 22 Wanda Filer, president of the American Academy of Family Physicians, told The BMJ that the academy supported the task force recommendations on depression screening.…”
Section: Featurementioning
confidence: 99%